2007
DOI: 10.4315/0362-028x-70.8.1966
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Escherichia coli O157:H7 in Leafy Vegetables

Abstract: Leafy vegetables, including lettuce and spinach, have been implicated in several outbreaks of foodborne disease caused by Escherichia coli O157:H7, a pathogen of increasing public health significance because of the severity of the gastrointestinal illness and long-term, chronic sequelae that can result from infection. A definitive association between the consumption of leafy vegetables and human disease provides implicit evidence of transfer from animal sources to field crops and retail commodities, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 78 publications
2
107
0
Order By: Relevance
“…This report is in agreement with the notion that infiltration of foodborne pathogens through stomata was considered a passive event (9,14,35). It was recently reported that vacuum cooling results in increased infiltration of E. coli O157:H7 into romaine lettuce tissue.…”
Section: Vol 75 2009supporting
confidence: 92%
See 2 more Smart Citations
“…This report is in agreement with the notion that infiltration of foodborne pathogens through stomata was considered a passive event (9,14,35). It was recently reported that vacuum cooling results in increased infiltration of E. coli O157:H7 into romaine lettuce tissue.…”
Section: Vol 75 2009supporting
confidence: 92%
“…Upon introduction to the leaf surface, both plant-and foodborne pathogens encounter multiple stresses, such as limited nutrients, UV irradiation, and desiccation (4,9,14,22,35). Although penetration of plant pathogens into leaf tissue was considered a passive mechanism (9,14,35), recent studies suggest that stomata play an active role in controlling internalization of both human and plant pathogens as part of the plant's innate immune system (24,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli O157:H7, one of the most important causative agents of fresh produce-associated outbreaks, is often linked with contaminated lettuce and spinach (11,12).…”
mentioning
confidence: 99%
“…However, studies performed with whole-cell bacterial biosensors for sucrose and fructose revealed heterogeneous distribution of these sugars on leaf surfaces, with few microsites harboring abundant quantities of them (8,22,28). In addition, rapid changes in water availability on the leaf surfaces of crops affect the solubility of nutrients that may be used by the plant microflora (15).…”
mentioning
confidence: 99%